Guest Editorial: Queering Girlhood. Issue 1 (1st March 2019) - Brickman, Barbara Jane
Abstract : In their new groundbreaking study reviewed in this special issue, The Trans Generation: How Trans Kids (and Their Parents) are Creating a Gender Revolution (2018), sociologist Ann Travers details the experiences of transgender children in the US and Canada, some as young as four years of age, who participated in research interviews over a five-year period. Establishing a unique picture of what it means to grow up as a trans child, Travers offers numerous examples of daily life and challenges for children like, for example, Martine and Esme, both of whom sought to determine their own gender at an early age: Martine and her family recount how at the age of seven she responded to her upcoming appointment at a gender clinic by asking if the doctor would have "the machine where you walk in as a boy and walk out as a girl, " while Esme's story begins in preschool and leads to the care of a "trans-affirmative doctor" (168) from the age of six and the promise of hormone blockers and estrogen at the onset of puberty. Although Travers's work is devoted to and advocates for trans children as a whole, its implications for our understanding of and research into girls and girlhood cannot be understated. What does it mean to "walk out" of that machine in the doctor's office "as a girl?" What happens when you displace the seemingly monumental onset of puberty from its previous biological imperatives and reproductive futures? How might feminist work on girlhoods, which has sought to challenge sexual and gender binaries for so long, approach an encounter with what Travers calls "binary-conforming" or "binary-identifying" (169) trans girls or with the transgender boys in their study who, at first, respond to the conforming pressures of adolescence very similarly to cisgender girls who will not ultimately transition away from a female identity?